Bidang Pendidikan Matematika: Indonesia - Ruslan, Rezky Rahma; Sitti Fatimah Sangkala Sirate; Syaharuddin; Ruslan B (ADPERTISI, 2022)
Teaching materials and learning media play an active role and are needed in the world of education. Moreover, the world has just been attacked with news of the covid-19 virus, which has resulted in teaching and learning to be carried out online. Many mediations are used by educators in enlightening the nation's children. Including learning strategies and the emergence of online learning media called LMS such as Moodle, Goggle classroom, Edmodo, Schoolagy, SevimaEdlink and there are also online applications such as Youtube and Whatsapps which can also be used in online learning. This activity was carried out in Kaba Village, Kec. District Commander. Pangkep and the participants were the surrounding community, totaling 17 people. The method of delivering material is in the form of lectures, discussions and simulations. The results of the activity show that socialization activities can increase public knowledge about teaching materials and learning media that can be used during the pandemic. Keywords: Teaching Materials, Learning Media, Learning Activities during the Pandemic Masa